NUEVAS DESCRIPCIONES PALINOLOGICAS DE LAS FORMACIONES SALAMANCA y BORORO, PALEOCENO DE CHUBUT (REPUBLICA ARGENTINA) (Ameghiniana, 2013)
The present paper deals with the description of 12 angiosperm pollen specíes and 1 Incertae Sedis found in Palaeocene sediments of the Chubut Province, Argentina. The material was collected from several sectíons of the Salamanca Formation (Cerro Abigarrado, Puerto Visser, Bajada de Hansen) and from other sections of the Bororó Formation. Samples from some subsurface cores have been studied too. The groups here described include monocolpate, tricolpate and tricolporate grains. The following new species are proposed . Liliacidites vermireticulatus, Spillizollocolpites hialinus, Bousea microreticulata, Bousea minuscola, Striatopollis exignus, Tricolpites bibaculotus. Psilatricolporites salamanquensis and Ericipites microtectatum.